The Effect of Clustering Technique on The Students’ Ability in Writing Descriptive Text at Grade Viii of SMP Negeri 4 Pematangsiantar - Siahaan, Ira Esrawaty (The Explora, 2020)
This research is aimed to know the effect of clustering technique on the students’ ability in writing descriptive text. Therefore, the researcher formulate a question as the problem. In order to answer the problems, some theories of experts were used, they are: Brown (2001), Checkett and Checkett (2006), Harmer (2004), Langan (2000), Patel and Jain (2008), Reid (1988), Richard and Renandya (2002). This research is quantitative research. This research was conducted byapplying Quasi-Experimental design. To answer the problem, grade VIII students of SMP Negeri 4 Pematangsiantar were used as the population and there were 60 students chosen as the sample of the research. It was chosen that grade VIII-5 students were chosen as the experimental group and VIII-9 as the control group. To analyze the data, the writer used IBMSPSS 20.0. From data analysis, mean of the writing score in experimental group is 77.95, meanwhile mean of the writing score in control group is 67.79. The result of analyzing the data shows the score of t-test is higher than t-table (4.12> 1.67). The hypothesis was accepted. Based on the analysis of data, it can be concluded that there is a significant effect of using clustering technique on